Coconut Shells, Water Hyacinth and Rice Husks are Very Effective in Improving the Quality of Physical and Chemical Standards of Dug Well Water in Flood Areas - Marlinae, Lenie; Biyatmoko, Danang; Husaini; Irawan, Chairul; Arifin, Syamsul; R Saidi, Akhmad; Fithria, Abdi; Zubaidah, Tien; M. Ratodi; A. Mourad, Khaldoon; Khairiyati, Laily; Waskito, Agung; H.D Lasari, Hadrianti; Khoiroh, Ianatul (Universitas Airlangga, 2024)
Introduction: Ensuring access to clean and safe drinking water is crucial, especially in flood-prone regions where the water quality in dug wells can deteriorate due to various physicochemical factors. This research was aimed to measure the effectiveness of natural materials in improving water quality based on physicochemical parameters and to compare water quality before and after treatment in Astambul Subdistrict of Banjar Regency, South Kalimantan Province. Methods: The study involved a survey of 192 private boreholes and dug wells across five villages in the Astambul Subdistrict, with 30 samples selected for detailed analysis. Key physicochemical parameters analyzed included total dissolved solids (TDS), dissolved oxygen (DO), turbidity, and total suspended solids (TSS). TDS, with a standard limit of 50 mg/L, served as a primary water quality indicator. DO, essential for gauging water oxygenation, and was measured as it results from photosynthesis and atmospheric absorption. Turbidity was assessed using a turbidimeter to determine water clarity, and a UV-vis Spectrophotometer 2008 was utilized to measure levels of iron (Fe) and mangasene (Mn). Results and Discussion: The findings demonstrated that coconut shells, husks, and water hyacinths improved water quality across physical and chemical parameters. Statistical analysis using t-tests showed improvements in these parameters after treatment. For example, DO levels increased in multiple villages, with the highest percentage in Kaliukan Village (59.2%) and decreases in turbidity and TSS. Conclusion: The study concluded that coconut shells, husks, and water hyacinths have potential to enhance physicochemical quality of water.